PENGEMBANGAN EKONOMI KREATIF DESA MELALUI BADAN USAHA MILIK DESA (BUMDES) MENUJU KOPERASI BERBASIS IT - HENDRO WIBOWO (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
The allocation of funds for villages from year to year has increased; the Government allocates Funds in 2015 amounting to Rp. 20 Trillion, in 2016 of Rp. 47 trillion, and in 2017 to Rp. 60 trillion. For the province of Banten in 2015 get funding of Rp. 200 billion, in 2016 to Rp. 791 Billion, and in the year 2017 of Rp. 1 trillion. This Village Fund requires financial management accountability (planning, implementation, administration, reporting, accountability, coaching and financial control). The purpose of the Fund's allocation is to establish a "Badan Usaha Milik Desa". The research aims to make the direction of development of the allocation of funds to be allocated for the creation of "Badan Usaha Milik Desa" with legal status of Cooperatives, and develop the potential of Village Economics based on Technology, Financial Technologi, and Market Place.